The potential role of soil amendments in increasing agricultural productivity and improving the livelihood of smallholders in Lao PDR - Mekuria, Wolde; Noble, A.D.; Hoanh, Chu Thai; McCartney, Matthew P.; Sengtaheuanghoung, Oloth; Sipaseuth, Nivong; Douangsavanh, Somphasith; Langan, Simon J.; Getnet, Kindie (2014)
The present study was undertaken in Lao PDR to investigate the impacts of organic and clay-based soil amendments on maize yield, total nutrient uptake and crop water productivity (CWP), and analyze the economic return of such interventions. Structured field experiments were established over two consecutive years (2011 and 2012) with maize as the test crop at the Veunkham and Naphok sites. Ten treatments were applied in a Randomized Complete Block Design with three replications. The treatments were control, rice husk biochar (applied at a rate of 10 t ha-1), bentonite clay (10 t ha-1), compost (4 t ha-1), clay-manure compost (10 t ha-1), rice husk biochar compost (10 t ha-1), and their combinations. All treatments were applied in 2011. CWP and the soil water balance of the various treatments were determined using the AquaCrop model. To determine the costs and benefits of soil amendments over the two cropping seasons a cost-based valuation method was applied. Significant (p < 0.05) treatment effects in maize grain yields, total nutrient uptake and CWP were observed. At Veunkham, differences in yield between the control and amended soils ranged from 0.9 to 3.3 t ha-1 in 2011 and from 0.2 to 1.3 t ha-1 in 2012, whereas differences at Naphok varied between 0.2 and 2.2 t ha-1 in 2011 and from 0.2 to 1.7 t ha-1 in 2012. Differences in CWP between the amended and control plots at Veunkham varied between 0.3 and 1.0 kg m-3 in 2011 and from 0.05 to 0.29 kg m-3 in 2012, whereas differences at Naphok varied between 0.1 and 0.6 kg m-3 in 2011 and from 0.1 to 0.4 kg m-3 in 2012. Differences between the control and amended soils in yield and the associated CWP can be attributed to the improvements in total N and P uptake, soil pH, exchangeable Ca++ and Mg++, and CEC following the application of soil amendments. At both sites, in most of the treatments, yields and CWP in 2012 were significantly (p < 0.05) lower than 2011. This difference can be attributed to late season drought. Over the two cropping seasons , the enhancement of maize yield due to soil amendments resulted in net revenues ranging from -794 to 841 and -331 to 1391 US$ ha-1 at Naphok and Veunkham, respectively. The study found that soils amended with low-cost amendments such as compost, rice husk biochar, rice husk biochar compost, and clay-manure compost were economically viable within the first cropping season. In contrast, soils amended with higher-cost amendments such as bentonite clay required up to 5 years to be economically viable. Such variations indicate that maize yield revenues alone are an insufficient incentive for farmers to adopt higher-cost soil amendments. The results of this study confirm that soil amendments can be effective in improving crop yield and the associated CWP. In addition, the income of smallholders can be improved using locally available low-cost soil amendments. These findings provide important information for decision makers wishing to improve agricultural productivity and food security through sustainable intensification.